Pengaruh Penggunaan Media Pembelajaran Interaktif Berbasis Powerpoint untuk Meningkatkan Motivasi Belajar, Kebiasaan Belajar, dan Hasil Belajar Siswa di SMK Negeri 3 Malang - Lizma Nur Saidah; Satrio Hadi Wijoyo; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The study was conducted based on observations over a period of one month of the condition of teaching and learning activities in SMK Negeri 3 Malang. During observation, the point of view of the problem is seen from the behavior of students. Problems that emerge are from the motivation and habits of students that are not good. Students always use powerpoint as their only learning resource. On the other hand, teaching books such as modules and e-books have been provided but are not utilized by students. The way out is to make modifications to the Powerpoint program into interactive media. Interactive means there is an interaction between powerpoint and students. The study was conducted by two class experimental methods, namely the control class and the experimental class. The instrument was a questionnaire and a pretest-posttest question. The instrument was analyzed using Pearson correlation test to determine the effect produced. The correlation test results stated that powerpoint interactive media had a positive effect on learning motivation by 44.22% while the other 55.78% were influenced by other factors. In the study habits there are 77.44% influence, another 22.56% influenced by other factors. In the learning outcomes of students there are 81.18% influence while the other 18.82% is influenced by other factors. So the authors suggest for educators to make more use of interactive powerpoint media in order to improve motivation and good study habits